2009
DOI: 10.1016/j.envsoft.2008.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of flow and dispersion properties of free and wall turbulent jets for source dynamics characterisation

Abstract: The objective of this paper is to provide an investigation, using large eddy simulations, into the dispersion of aircraft jets in co-flowing take-off conditions. Before carrying out such study, simple turbulent plane free and wall jet simulations are carried out to validate the computational models and to assess the impact of the presence of the solid boundary on the flow and dispersion properties.The current study represents a step towards a better understanding of the source dynamics behind an airplane jet e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Similarly to the previous time level and recalling some of the discussions presented by [2] and [4], it was found that the near field is very much influenced by the spanwise direction vortices and these were found to be the ones that act as conveyors to disperse the plume downwind. As these vortices start to decrease in magnitude, a transition was observed.…”
Section: Vortical Structure Studymentioning
confidence: 86%
See 4 more Smart Citations
“…Similarly to the previous time level and recalling some of the discussions presented by [2] and [4], it was found that the near field is very much influenced by the spanwise direction vortices and these were found to be the ones that act as conveyors to disperse the plume downwind. As these vortices start to decrease in magnitude, a transition was observed.…”
Section: Vortical Structure Studymentioning
confidence: 86%
“…The details of the numerical solver are explained in previous papers [4,2]. Validation tests were also presented for the case of free and wall jets [2], and will not be repeated here.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations